Valsartan Attenuates Atherosclerosis via Upregulating the Th2 Immune Response in Prolonged Angiotensin II–Treated ApoE(−/−) Mice - Meng, Kai (Mol Med, 2015)
Valsartan has a protective effect against hypertension and atherosclerosis in humans and experimental animal models. This study aimed to determine the effect of prolonged treatment with angiotensin II (Ang II) on atherosclerosis and the effect of valsartan on the activity of CD4(+) T lymphocyte subsets. The results showed that prolonged treatment (8 wks) with exogenous Ang II resulted in an increased atherosclerotic plaque size and a switch of stable-to-unstable plaque via modulating on CD4(+) T lymphocyte activity, including an increase in the T helper cell type 1 (Th1) and Th17 cells and a decrease in Th2 and regulatory T (Treg) cells. In contrast, valsartan treatment efficiently reversed the imbalance in CD4(+) T lymphocyte activity, ameliorated atherosclerosis and elicited a stable plaque phenotype in addition to controlling blood pressure. In addition, treatment with anti-interleukin (IL)-5 monoclonal antibodies weakened the antiatherosclerotic effects of valsartan without affecting blood pressure.